The Effect of Using Gamification In English Learning At SMA Negeri 5 Takalar - Irfani, Nur; Akib , Erwin; Latief, Hasnawati (Journal of Computer Interaction in Education, 2025)
This study investigates the effectiveness of the Gamification strategy in enhancing reading comprehension among Grade 11 students at SMA Negeri 5 Takalar. As innovative, student-centered approaches become increasingly urgent in modern education, this research offers empirical insight into the application of gamification in language learning. A quasi-experimental quantitative design was employed, involving 30 purposively selected students. Data were collected through pre- and post-tests administered to both experimental and control groups. Results show a substantial improvement in the experimental group’s reading scores (from 50.53 to 89.20), compared to the control group (from 48.53 to 64.93). Statistical analysis revealed a significant difference (p = 0.000 < 0.05), and the effect size of 2.3 indicates a strong impact. These findings demonstrate that the Gamification strategy significantly improves reading comprehension and contributes to the development of engaging, effective English learning practices in secondary education.